1991
DOI: 10.1055/s-2006-960125
|View full text |Cite
|
Sign up to set email alerts
|

Lepenine and Denudatine: New Alkaloids fromAconitum kusnezoffii

Abstract: The diterpenoid alkaloids aconitine, deoxyaconitine, hypaconitine, mesaconitine, and beiwutine have been isolated from the roots of Aconitwn kusnezoffli Reichb. (Ranunculaceae) (1). Besides these bases, we have isolated compounds 1 and 2 from the aerial parts of A. kusnezoffli collected in Mongolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 1 publication
(1 reference statement)
0
13
0
1
Order By: Relevance
“…Herein, we describe the isolation and structural elucidation of the two new compounds. 4,5 The 1D NMR spectral data (Table 1) were similar to those of denudatine 6 except that there was an N=CH group in compound 1, instead of the NCH 2 CH 3 in denudatine. The existence of a double bond between the N and C-19 was finally verified by the HMBC correlations (Figure 2) between the olefinic proton of H-19 (δ H 7.29, br.s) and C-3, C-4, C -5, C-18 and C-20.…”
Section: Introductionmentioning
confidence: 67%
“…Herein, we describe the isolation and structural elucidation of the two new compounds. 4,5 The 1D NMR spectral data (Table 1) were similar to those of denudatine 6 except that there was an N=CH group in compound 1, instead of the NCH 2 CH 3 in denudatine. The existence of a double bond between the N and C-19 was finally verified by the HMBC correlations (Figure 2) between the olefinic proton of H-19 (δ H 7.29, br.s) and C-3, C-4, C -5, C-18 and C-20.…”
Section: Introductionmentioning
confidence: 67%
“…C-NMR spectrum suggested that the two moieties of this bis-C 20 -diterpenoid alkaloid consist of a denudatine-type C 20 -diterpenoid-alkaloid moiety and an atisine-type C 20 -diterpenoid-alkaloid moiety [1]. Comparison of the NMR data of the denudatine moiety of piepunine with those of denudatine [7], a representative denudatine-type C 20 -diterpenoid alkaloid, revealed that they shared a similar NMR spectral pattern. The presence of the denudatine moiety was confirmed by the correlations Me(18)/C(19), CH 2 (19)/C(20), HÀC(20)/C(8), and HÀC(7)/C(10) in the HMBC spectrum (Fig.…”
mentioning
confidence: 89%
“…由于植物的 产地、气候等因素对其化学成分影响较大, 2008 年, 谭 宁 华 等 [3] 报 道 了 从 该 植 物 中 分 离 得 到 一 个 具 C(8)-C(9)-C(10)三元环体系的新骨架的 C 19 -二萜生物碱. 为了更好的开发利用我国乌头属植物的药用资源, 本课 题组对其进行更深入的系统研究, 从该植物中共分离得 到 20 个化合物(Scheme 1), 其中一个为新的 C 19 二萜生 物碱 epi-16β-hydroxycardiopetaline (1), 其余 19 个已知 化合物分别为: talatisamine (2) [4] , karakoline (3) [5] , sachaconitine (4) [6] , 14-O-veratroylneoline (5) [7] , vilmorrianine A (6) [8] , yunaconitine (7) [9] , condelphine (8) [10] , 14-acetyl-sachaconitine (9) [11] , indaconitine (10) [12] , 14-acetylkarakoline (11) [13] , 14-acetyltalatizamine (12) [14] , cammaconine (13) [15] , isotalatizidine (14) [16] , 8-deacetylyunaconitine (15) [17] , 16β-hydroxycardiopetaline (16) [18] , pseudaconine (17) [19] , columbianine (18), denudatine (19) [20] , panicutine (20) [21] . 新 化 合 物 的 结 构 应 用 HRESIMS, 1D-和 2D-NMR, 单晶 X 射线衍射等方法予 以确证.…”
unclassified